2023
DOI: 10.1037/hea0001254
|View full text |Cite
|
Sign up to set email alerts
|

Family- and neighborhood-level environmental associations with physical health conditions in 9- and 10-year-olds.

Abstract: Objective: To determine how environmental factors are associated with physical health conditions in 9-to 10-year-old participants in the Adolescent Brain Cognitive Development (ABCD) Study, and how they are moderated by family-level socioeconomic status (SES). Method: We performed cross-sectional analyses of 8,429 youth participants in the ABCD Study, in which nine physical health conditions (having underweight or overweight/obesity, not participating in sports activities, short sleep duration, high sleep dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…At a minimum, investigators and clinicians should ask about whether the individual at the focus of treatment lives alone and, if so, how available (both geographically and in terms of time) other caregivers are (Sweegers et al, 2019;Fearnbach et al, 2021;Tsuji, 2022;Tanaka et al, 2023). A related and increasingly available metric to assess structural support are emerging area deprivation indices, which provide information on environmental impoverishment that appear to predict health behavior outcomes over and above family income levels (Steppuhn et al, 2019;Melo et al, 2021;Congdon, 2022;Marshall et al, 2023;Witkam et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…At a minimum, investigators and clinicians should ask about whether the individual at the focus of treatment lives alone and, if so, how available (both geographically and in terms of time) other caregivers are (Sweegers et al, 2019;Fearnbach et al, 2021;Tsuji, 2022;Tanaka et al, 2023). A related and increasingly available metric to assess structural support are emerging area deprivation indices, which provide information on environmental impoverishment that appear to predict health behavior outcomes over and above family income levels (Steppuhn et al, 2019;Melo et al, 2021;Congdon, 2022;Marshall et al, 2023;Witkam et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies, including some in this special issue (see papers led by Adise et al, 2023; Marshall et al, 2023), have found that adverse neighborhood and environmental factors can lead to adverse biopsychosocial outcomes. Adise et al (2023) Adise and colleagues found support for the associations between neighborhood deprivation, brain structure, and childhood obesity.…”
Section: Overview Of Papers In the Special Issuementioning
confidence: 99%
“…In addition to neighborhood deprivation, Marshall et al (2023) examined whether environmental factors were associated with physical health conditions among 9- to 10-year-olds, and how this relationship was moderated by family-level socioeconomic status. They found that exposure to neurotoxicants including lead and particulate matter was associated with various physical health outcomes including increased odds of unhealthy weight gain, reduced sports and physical activity, and short sleep duration.…”
Section: Overview Of Papers In the Special Issuementioning
confidence: 99%